Pediatric meningitis due to Neisseria meningitidis, Streptococcus pneumoniae and Group B Streptococcus in Tijuana, Mexico: active/prospective surveillance, 2005–2018. (March 2019) - Chacon-Cruz, Enrique; Roberts, Christopher; Rivas-Landeros, Rosa Maria; Lopatynsky-Reyes, Erika Zoe; Almada-Salazar, Lucila Alejandra; Alvelais-Palacios, Jorge Arturo
Introduction: In Mexico, Neisseria meningitidis is considered to be a rare cause of bacterial meningitis (BM), however, one national publication using active surveillance has suggested the opposite. Group B Streptococcus (GBS) is also considered to be infrequent in young infants as a cause of BM in central Mexico. Streptococcus pneumoniae vaccination using the 13-valent conjugate vaccine (PCV13) started in our region in May 2012. We focused our research on whether N. meningitidis and GBS are important causes of BM, and to examine the effectiveness of PCV13 on pneumococcal BM. Methods: From October 2005 to September 2018, active/prospective surveillance looking for all patients admitted with suspected BM <16 years of age was performed at the Tijuana, Mexico, General Hospital. Tijuana, Mexico to San Diego, Unites States of America (USA), is the most transited border in the world. Isolation of pathogens was by either conventional culture or Real Time-polymerase chain reaction (RT-PCR), all patients were followed during and 3 months after discharge, and a descriptive analysis was performed. The effectiveness of PCV13 was determined by comparing the proportion of cases per month on pneumococcal BM before and after its implementation. Results: There were 86 confirmed BM cases. N. meningitidis was the leading cause (60.5%, and 61.5% caused by serogroup C), followed by S. pneumoniae (18.6%). PCV13 effectiveness on pneumococcal BM was of 64.3% and was associated with the disappearance of serotype 19A. A total of 22 infants <3 months old had BM; GBS was the leading cause at this age group (27.3%), followed by N. meningitidis (22.7%). The overall mortality was 24%. Conclusions: BM by N. meningitidis is endemic in Tijuana, Mexico, and meningococcal vaccination should be seriously considered in the region. PCV13 is currently showing high effectiveness on pneumococcal BM, and we need to continue active surveillance to see whether maternal screening/prophylaxis for GBS should also be introduced in the region.